2015
DOI: 10.1039/c4ra13410a
|View full text |Cite
|
Sign up to set email alerts
|

Bio-templated synthesis of hierarchically ordered macro-mesoporous anatase titanium dioxide flakes with high photocatalytic activity

Abstract: Hierarchically ordered macro-mesoporous anatase TiO2 flakes were synthesized by using rose petals and P123 as dual templates with high photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Since Fujishima and Honda first demonstrated that TiO 2 was a promising photo-anode for UV light-driven photocatalytic water splitting [34], which has been widely studied in many photocatalytic reactions due to its chemical stability, low cost, environmentally friendly nature, and tunable electronic energy band gap [143,144,145,146,147]. Figure 4 shows a band gap illustration of TiO 2 .…”
Section: Photocatalyst Materialsmentioning
confidence: 99%
“…Since Fujishima and Honda first demonstrated that TiO 2 was a promising photo-anode for UV light-driven photocatalytic water splitting [34], which has been widely studied in many photocatalytic reactions due to its chemical stability, low cost, environmentally friendly nature, and tunable electronic energy band gap [143,144,145,146,147]. Figure 4 shows a band gap illustration of TiO 2 .…”
Section: Photocatalyst Materialsmentioning
confidence: 99%
“…Besides, the size of the secondary pore can be fine-tuned from 0.9 to 4.8 nm by changing the crystallization temperature and Ti/Si ratio [ 57 , 58 ]. To better control the hierarchically porous structures, colloidal crystals constructed by SiO 2 or polymer nanospheres were introduced as the hard templates [ 59 , 60 ]. For example, Su and coworkers have synthesized ordered hierarchically mesoporous TiO 2 microparticles by using P(St-MMA-SPMAP) spheres and P123 as the hard and soft templates, respectively (Fig.…”
Section: Diverse Architecturesmentioning
confidence: 99%
“…In addition to the improved charge transfer reaction, an enhanced light harvesting capability can be ensured due to the multireflection within interconnected open networks. Among the studied por-ous photocatalysts, nano/mesoporous systems have constituted the major part, but they are still deeply limited by the narrow pore sizes that are not effective for significant mass transport and access [27]. Making highly macroporous system seems a satisfactory solution of this aspect, especially when the issue on the significant loss of specific surface area (SSA) is well addressed.…”
Section: Introductionmentioning
confidence: 99%